Real‐World Study of Everolimus in Advanced Progressive Neuroendocrine Tumors. (12th August 2014) - Panzuto, Francesco; Rinzivillo, Maria; Fazio, Nicola; de Braud, Filippo; Luppi, Gabriele; Zatelli, Maria Chiara; Lugli, Francesca; Tomassetti, Paola; Riccardi, Ferdinando; Nuzzo, Carmen; Brizzi, Maria Pia; Faggiano, Antongiulio; et al.
Abstract : Everolimus is a valid therapeutic option for neuroendocrine tumors (NETs); however, data in a real‐world setting outside regulatory trials are sparse. The aim of this study was to determine everolimus tolerability and efficacy, in relation to previous treatments, in a compassionate use program. A total of 169 patients with advanced progressive NETs treated with everolimus were enrolled, including 85 with pancreatic NETs (pNETs) and 84 with nonpancreatic NETs (non‐pNETs). Previous treatments included somatostatin analogs (92.9%), peptide receptor radionuclide therapy (PRRT; 50.3%), chemotherapy (49.7%), and PRRT and chemotherapy (22.8%). Overall, 85.2% of patients experienced adverse events (AEs), which were severe (grade 3–4) in 46.1%. The most frequent severe AEs were pneumonitis (8.3%), thrombocytopenia (7.7%), anemia (5.3%), and renal failure (3.5%). In patients previously treated with PRRT and chemotherapy, a 12‐fold increased risk for severe toxicity was observed, with grade 3–4 AEs reported in 86.8% (vs. 34.3% in other patients). In addition, 63.3% of patients required temporarily everolimus discontinuation due to toxicity. Overall, 27.8% of patients died during a median follow‐up of 12 months. Median progression‐free survival (PFS) and overall survival (OS) were 12 months and 32 months, respectively. Similar disease control rates, PFS, and OS were reported in pNETs and non‐pNETs. In the real‐world setting, everolimus is safe and effective for the treatment of NETs of different origins. Higher severe toxicity occurred in patients previously treated with systemic chemotherapy and PRRT. This finding prompts caution when using this drug in pretreated patients and raises the issue of planning for everolimus before PRRT and chemotherapy in the therapeutic algorithm for advanced NETs. Abstract : The aim of this study was to determine everolimus tolerability and efficacy, in relation to previous treatments, in a compassionate use program for neuroendocrine tumors (NETs). Results showed that everolimus is safe and effective for the treatment of NETs of different origins. Higher severe toxicity occurred in patients previously treated with systemic chemotherapy and peptide receptor radionuclide therapy.